Sistem Informasi Antrian pada Klinik Nabila Dental Menggunakan Algoritma First Come Fisrt Served (FCFS) - Ryan Hidayat; Farida Yusuf; Nahrun Hartono (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Nabila Dental Clinic is a dental health service provider that previously implemented a conventional queuing system, where patients had to come directly to take the queue number and come back at different times to undergo the examination. This system poses various problems, such as wasting time, additional costs, patient discomfort, and inefficiencies in services. This research aims to design and implement a web-based queuing information system to overcome these problems. The system is built using the First Come First Served (FCFS) algorithm that prioritizes fairness and simplicity in queue distribution, as well as the Rapid Application Development (RAD) software development method that emphasizes speed and user engagement through the stages of needs analysis, design, prototyping, and system testing. Data collection techniques include direct observation in the field, interviews with related parties, and literature studies to support the design of the system. The results of the study show that the web-based queue information system is able to provide real solutions to the problems faced by Nabila Dental Clinic. The online queue number collection feature allows patients to make queue bookings without having to come in person, reducing waiting times and improving service efficiency. The system test with the User Acceptance Testing (UAT) method obtained a user acceptance rate of 84.34%, while the system efficiency aspect scored 4.51 on a scale of 5, which indicates that the system is classified as very efficient. In addition to technical aspects, this system also reflects Islamic values such as justice and convenience in health services. Thus, the implementation of this system is expected to be a strategic step towards the digitization of services that are sustainable, efficient, and oriented towards patient satisfaction at Nabila Dental Clinic.